Study of an ADS Loaded with Thorium and Reprocessed Fuel - Graiciany de Paula Barros; Claubia Pereira; Maria A. F. Veloso; Antonella L. Costa (Science and Technology of Nuclear Installations)
Accelerator-driven systems (ADSs) are investigated for long-lived fission product transmutation and fuel regeneration. The aim of this paper is to investigate the nuclear fuel evolution and the neutronic parameters of a lead-cooled accelerator-driven system used for fuel breeding. The fuel used in some fuel rods was T232hO2 for U233 production. In the other fuel rods was used a mixture based upon Pu-MA, removed from PWR-spent fuel, reprocessed by GANEX, and finally spiked with thorium or depleted uranium. The use of reprocessed fuel ensured the use of T232hO2 without the initial requirement of U233 enrichment. In this paper was used the Monte Carlo code MCNPX 2.6.0 that presents the depletion/burnup capability, combining an ADS source and kcode-mode (for criticality calculations). The multiplication factor (keff) evolution, the neutron energy spectra in the core at BOL, and the nuclear fuel evolution during the burnup were evaluated. The results indicated that the combined use of T232hO2 and reprocessed fuel allowed U233 production without the initial requirement of U233 enrichment.